SITR Model of Tuberculosis Spread in Makassar City - Fadhilah, Helisyah Nur; Annur, Ahmad Ihda Falah; Oktavia, Eka Putri (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
ABSTRACTTuberculosis or TBC is a type of chronic infectious disease caused by bacteria called Mycobacterium tuberculosis. The disease poses a serious threat to health regardless of age or gender. Individuals infected with this disease will experience symptoms such as coughing with sputum or blood, chest pain, and high fever. Transmission occurs through aerosols and droplets, allowing the bacteria to spread through the air and requires a minimum of 6 months of treatment for recovery. Therefore, The SITR (Suspectible-Infective-Treatment-Recovered) mathematical model with the Euler method is appropriately used in this article to describe the condition where infected individuals need treatment for recovery. The data analyzed comes from tuberculosis case reports collected by the South Sulawesi Regional Health Agency in 2015. This research has important relevance in understanding the dynamics of TB spread and provides a basis for the development of disease spread strategies. By using mathematical models, key factors affecting the spread of tuberculosis can be identified. Keywords: Mathematical Model, SITR Model, Dynamics of Spread, Tuberculosis.